Chewing Aid in Routine Postoperative Orders - Does it reduce Postoperative Ileus after Cesarean Section? A Randomized Control Trial - Ali, Aun; Saeed, Summaya; Memon, Amjad Siraj; Abbasi, Mujeeb; Samo, Khursheed; Mustafa, Rozina (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To assess effectiveness of chewing gum in women undergoing cesarean section (C-Section) on return of bowel movements. METHODOLOGY: Randomized clinical trial was conducted at a tertiary care hospital, Karachi from January 2013 to January 2016. Total 218 participants, who were planned for Cesarean section, were randomly allocated into two groups, 109 participants in each group. In Group-I, patient’s received chewing gum as routine and group II was control group. Data of all subjects were analyzed using SPSS version 20. RESULTS: The mean age of participants was 22.68±6.31 years. There was no significant difference between both groups in terms of age, Body Mass index, duration of surgery, parity, number of miscarriages and type of cesarean section whether elective or emergency. Significant reduction was found in terms of onset of defecation (P<0.001), onset of first flatus passed (P<0.001) and feeling of hunger (P<0.003) between two groups. CONCLUSION: The current study identified that routine use of chewing gum as postoperative order impacts positively on time of passing flatus, defecation, and feeling of hunger. Eventually, it will reduce suffering resulting from ileus fostering early feeding. Since it is non-expensive and easy to use method therefore, it can be included as a routine post-operative management for women undergoing cesarean section. However, it is recommended to investigate impact of using chewing gum in other abdominal surgeries.